Propiedades Fisicoquímicas y Térmicas del Almidón extraído de papa nativa (solanum tuberosum l.) variedad santa rosa cultivada en el Distrito de Chugay – Provincia de Sánchez Carrión - Quezada Moncada, Asthry Jane (2017)
The objective of this study was to determine the physicochemical and thermal properties of starch extracted from Santa Rosa native potato of the Chugay district of the province of Sánchez Carrión. Moisture and ash were determined according to AOAC, the percentage of transmittance and amylose content by spectrophotometry, shape and size of the granules by microscopy, besides swelling power, solubility, stability in refrigeration and freezing, gel firmness, and their thermal properties of temperature And enthalpy of gelatinization using differential scanning calorimetry. Values of 11.01 ± 0.01%, 0.26 ± 0.03%, 21.31 ± 1.98% and 78.69% were found for moisture, ash, amylose and amylopectin contents, respectively. The shape of the starch granules was ovoid and their average size was 57.1610 ± 3.8973 μm and 3.6168 ± 1.092 μm, for the large and small granules, respectively. It presented low swelling and solubility, values that were increased with the increase of temperature, obtained 27.23 ± 0.76 g water / g starch and 4.01 ± 0.70% at 90 ° C. Statistical difference (p <0.05) was found for swelling power results, however there was no difference for solubility results. In addition, the starch showed high clarity (40.37 ± 0.66%), low firmness (0.007 ± 0.000 kg / f), low freezing stability (29.01 ± 4.76% at 12.85 ± 1.96%) and low gelatinization temperature (Tp: 62.04 ± 0.04 ° C). By the evaluated properties they may be considered to be used in products which do not require high processing temperatures, such as soft candies or custards, puddings, as thickening agents and stabilizers in those foods which need to be stored in refrigeration and require some moisture exudation to provide A fresh appearance, such as flans or sauces.